2022
DOI: 10.1007/s00018-022-04335-w
|View full text |Cite
|
Sign up to set email alerts
|

Trigeminal neurons control immune-bone cell interaction and metabolism in apical periodontitis

Abstract: Apical periodontitis (AP) is an inflammatory disease occurring following tooth infection with distinct osteolytic activity. Despite increasing evidence that sensory neurons participate in regulation of non-neuronal cells, their role in the development of AP is largely unknown. We hypothesized that trigeminal ganglia (TG) Nav1.8+ nociceptors regulate bone metabolism changes in response to AP. A selective ablation of nociceptive neurons in Nav1.8Cre/Diphtheria toxin A (DTA)Lox mouse line was used to evaluate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 61 publications
3
16
0
Order By: Relevance
“…Transgenic rats with interleukin-6 overexpression have bone loss and increased bone absorption [ 31 ]. Recently, according to relevant literature, IL-6 promotes bone resorption by inducing the proliferation of osteoclasts along the RANKL/RANK/OPG axis [ 32 ]. IL-6 can raise the expression of RANKL in osteoblasts [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Transgenic rats with interleukin-6 overexpression have bone loss and increased bone absorption [ 31 ]. Recently, according to relevant literature, IL-6 promotes bone resorption by inducing the proliferation of osteoclasts along the RANKL/RANK/OPG axis [ 32 ]. IL-6 can raise the expression of RANKL in osteoblasts [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…CD68 has been indicated as a marker of all the activated macrophages in the sensory ganglion. 27 The results showed that CFA administration significantly increase the number of macrophages (compared to the saline control, P < 0.0001). Sympathectomy markedly reduced the number of macrophages infiltrated in the TG after the induction of orofacial inflammation (105.7 ± 7.4 in SYM group versus 138.1 ± 5.7 in CFA group, P < 0.01, Figure 2A and B ).…”
Section: Resultsmentioning
confidence: 91%
“…We found that nociceptor ablation results in an earlier increase in inflammation, as shown by the upregulation of key cytokines and a greater influx of macrophages and lymphocytes. In addition, we have shown that nociceptors directly regulate osteoblastic and osteoclastic functions, demonstrating direct communication with bone metabolism cells 8 . While the progression of AP inflammatory responses had been previously characterized 13 , the overall transcriptomic profiling of this process and its regulation by nociceptors is unknown.…”
Section: Introductionmentioning
confidence: 94%
“…As such, we have recently shown that in a rodent model of apical periodontitis (AP), nociceptors are osteoprotective by attenuating bone loss after infection when compared to nociceptor-ablated rodents 8 , 9 . We found that nociceptor ablation results in an earlier increase in inflammation, as shown by the upregulation of key cytokines and a greater influx of macrophages and lymphocytes.…”
Section: Introductionmentioning
confidence: 99%